Effect of plant growth regulators on the growth and direct shoot formation from leaf explants of the hybrid Phalaenopsis ‘Pink’ - Avishek DATTA; Meutia ZAHARA; Patchareeya BOONKORKAEW; Abha MISHRA (Acta Agriculturae Slovenica)
Phalaenopsis orchids are one of the most beautiful flowering plants. The objective of this study was to identify the best plant growth regulator combination and medium for the growth and direct shoot formation from leaf explants of the hybrid Phalaenopsis ‘Pink’. Leaf tips segments from in vitro young plants were cultured on half-strength Murashige and Skoog (MS) and Vacin and Went (VW) media supplemented with different concentrations of auxin [α-napthaleneacetic acid (NAA)] and cytokinins [6-benzylaminopurine (BAP) or thidiazuron (TDZ)]. The explants that were cultured on 0 mg l–1 NAA and 3 mg l–1 BAP supplemented to half-strength MS medium formed shoots successfully within 10 weeks of culture with 5 % regenerants and 50 % survival frequency. The explants cultured on 0.5 mg l–1 NAA and 1.5 mg l–1 TDZ supplemented to half-strength MS medium developed calluses and shoots within 11 weeks of culture with 25 % regenerants and 90 % survival frequency. Future research needs to be directed to find out the shortest time of shoot regeneration to produce viable plants with a high survival frequency.